Cancer and immune-mediated necrotizing myopathy: a longitudinal referral case-controlled outcomes evaluation. (14th March 2022) - Shelly, Shahar; Beecher, Grayson; Milone, Margherita; Liewluck, Teerin; Ernste, Floranne; Triplett, James; Naddaf, Elie; Zekeridou, Anastasia; McKeon, Andrew; Pittock, Sean J; Dubey, Divyanshu; Mills, John R; et al.
Abstract: Objectives: To investigate immune-mediated necrotizing myopathy (IMNM) association with cancer and its clinical implications. Methods: IMNM cases were identified 1 January 2000 to 31 December 2020 matching sex and age controls (4:1). Results: A total of 152 patients with IMNM were identified and among serologically tested, 60% (83/140) were HMGCR-IgG+, 14% (20/140) were SRP-IgG+ and 26% (37/140) were seronegative. Cancer rates were not significantly different between serological subgroups; 18.1% (15/83) HMGCR-IgG+, 25% (5/20) SRP-IgG+ and 30% (11/37) seronegative ( P = 0.34). Cancer screening was performed within 12 months from IMNM diagnosis in 88% (134/152) (whole-body CT plus FDG-PET CT in 53, CT alone in 72 and FDG-PET alone in 9). FDG-PET/CT was positive in 73% (25/34) of cancers. Increasing age was the only risk associated with cancer ( P = 0.02). The odds of developing cancer at ±3 or ±5 years from IMNM diagnosis was not higher than controls (OR = 0.49; CI: 0.325–0.76). Lifetime IMNM diagnosis of cancer was less compared with controls (OR = 0.5 CI: 0.33–0.78, P = 0.002). Most patients responded to treatment (137/147, P < 0.001). Death and treatment response did not significantly differ between cancer [23% (8/34); 88% (29/33)] and non-cancer patients [19% (23/118); 92% (108/118)]. In total, 13% (20/152) of patients died during follow-up compared with 14% (41/290) of medicine and 16% (46/290) of neurology controls ( P = 0.8). Seropositives had greater life expectancy than seronegatives ( P = 0.01). Conclusions: Greater cancer risk is not observed in IMNM vs controls. Cancer screening in IMNM should be individualized based on age-personal and family history, including consideration of FDG-PET/CT. Immune-treatment response did not differ with cancer.